Women's Reproductive Mental Health Across the Lifespan
XXVII, 333 p. 1 illus. in color.
Keywords: This outstanding collection of work is an important, timely, and much needed resource. Dr. Diana Lynn Barnes has been instrumental in bringing attention to the needs of perinatal women for decades. In Women's Reproductive Health Across the Lifespan, she brilliantly unites the medical world of reproductive life events with the psychiatric and psychological world of mental health issues associated with them. Her expertise, combined with contributions by distinguished leaders in the field, create a volume of work that should be studied carefully by every medical and mental health provider who works with women. -Karen Kleiman, MSW, The Postpartum Stress Center, Author of Therapy and the Postpartum Woman Finally, a book that addresses the entire scope of women’s reproductive mental health spanning the gamut from puberty to menopause. The list of chapter contributors reads like a who’s who of international experts. Unique to this book is its focus onthe interaction of genetics, hormonal fluctuations, and the social environment. It is a must addition for the libraries of clinicians and researchers in women’s reproductive mental health. -Cheryl Tatano Beck, DNSc, CNM, FAAN, Board of Trustees Distinguished Professor, School of Nursing, University of Connecticut Pregnancy and childbirth are generally viewed as joyous occasions. Yet for numerous women, these events instead bring anxiety, depression, and emotional distress. Increased interest in risk reduction and early clinical intervention is bringing reproductive issues to the forefront of women's mental health. The scope of Women's Reproductive Mental Health across the Lifespan begins long before the childbearing years, and continues well after those years have ended. Empirical findings, case examples, and dispatches from emerging areas of the field illuminate representative issues across the continuum of women's lives with the goal of moreeffective care benefitting women and their families. Chapter authors discuss advances in areas such as fertility treatment and contraception, and present current thinking on the psychological impact of pregnancy loss, menopause, cancer, and other stressors. These expert contributors emphasize the connections between an individual's biology and psychology and cultural expectations in shaping women's mental health, and the balance between a client's unique history and current clinical knowledge clinicians need to address disorders. Included in the coverage: The experience of puberty and emotional wellbeing. Body image issues and eating disorders in the childbearing years. Risk assessment and screening during pregnancy. Normal and pathological postpartum anxiety. Mood disorders and the transition to menopause. The evolution of reproductive psychiatry. A reference with an extended shelf life, Women's Reproductive Mental Health across the Lifespan enhances the work of researchers and practitioners in social work, clinical psychology, and psychiatry, and has potential relevance to all health care professionals.